2017
DOI: 10.7704/kjhugr.2017.17.4.208
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study ofHelicobacter pyloriGrowth on Different Agar-based Media

Abstract: Background/Aims: Optimal culture conditions for Helicobacter pylori have not been established. We compared the effectiveness of four different agar-based media for the growth of H. pylori. Materials and Methods: G27, ATCC #43504 and 60190, and primary cultured strains were used. H. pylori strains were cultured for four days under four culture conditions: chocolate agar, Thayer-Martin (TM) agar containing vancomycin-colistin-nystatin inhibitor (VCNI), Brucella agar, and brain heart infusion (BHI) agar containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…It is assumed that AMPKs evolved in the early eukaryote to control the output of carbohydrates produced by acquired bacterial endosymbionts that developed into mitochondria but were thought not to play a role in bacteria [106][107][108]. However, AMPKs were isolated from L. pneumophila [21], H. pylori [22][23][24], Mycobacterium spp., B. subtilis, L. monocytogenes, and rhizobial bacteria [109][110][111][112] and were involved in sensitization of resistant bacteria to antibiotics, too [10,70,[83][84][85]. Bacterial AMPKs may be inhibited by metformin.…”
Section: Inhibition Of Bacterial Serine/threonine/tyrosine Protein Kimentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that AMPKs evolved in the early eukaryote to control the output of carbohydrates produced by acquired bacterial endosymbionts that developed into mitochondria but were thought not to play a role in bacteria [106][107][108]. However, AMPKs were isolated from L. pneumophila [21], H. pylori [22][23][24], Mycobacterium spp., B. subtilis, L. monocytogenes, and rhizobial bacteria [109][110][111][112] and were involved in sensitization of resistant bacteria to antibiotics, too [10,70,[83][84][85]. Bacterial AMPKs may be inhibited by metformin.…”
Section: Inhibition Of Bacterial Serine/threonine/tyrosine Protein Kimentioning
confidence: 99%
“…Copper complexation may also contribute to the antihyperglycaemic action of metformin [19,20]. Metformin exerted effects not only on the gut microbiome but also against Legionella pneumophila [21] and H. pylori [22][23][24] and several other bacterialand viral species [25] in vitro, in vivo and in the clinical setting. Proposed mechanisms of antibacterial action encompass those effects attributed to antihyperglycaemic effects of metformin, inhibition of electron transport, and also AMPK independent effects such as immunomodulation, or production of mitochondrial reactive oxygen species thus enhancing bactericidal activities of macrophages [25,26].…”
mentioning
confidence: 99%
“…When comparing with the number of positives obtained by antigenic screening, it can be suggested that the culture method allows determining if the microorganism detected by screening test is viable in the plate, in such a way that the number of viable samples is lower than antigenic screening. In a study conducted by Lee et al (29) after comparing some culture methods from biopsy samples, they determined that the culture media, Thayer agar, Brucella agar, Chocolate agar, and Brain heart infusion agar acted in the same way, obtaining similar results under conditions of 10% CO 2 and 96% humidity at 37°C. Similarly, in a work carried out by Xu et al (30) it was determined that in Brucella agar, chocolate agar and brain heart infusion, H. pylori agar has the ability to live up to 56 days.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were washed once with sterile PBS, and then two H. pylori strains (60190 from ATCC, and G27, kindly provided by Prof. Nayoung Kim, Seoul National University, Korea) were added at a multiplicity of infection (MOI) of 100:1 for different time points, followed by washing with PBS six times to remove nonadherent bacteria. Isogenic mutants lacking CagA (60190DA) or CagE (G27DE) were used as described previously (19,20).…”
Section: H Pylori Infection Of Hfe 145 Cellsmentioning
confidence: 99%